Significantly enhanced thermal conductivity of indium arsenide nanowires via sulfur passivation. Issue 1 (December 2017) - Xiong, Yucheng; Tang, Hao; Wang, Xiaomeng; Zhao, Yang; Fu, Qiang; Yang, Juekuan; Xu, Dongyan
Abstarct In this work, we experimentally investigated the effect of sulfur passivation on thermal transport in indium arsenide (InAs) nanowires. Our measurement results show that thermal conductivity can be enhanced by a ratio up to 159% by sulfur passivation. Current-voltage (I-V) measurements were performed on both unpassivated and S-passivated InAs nanowires to understand the mechanism of thermal conductivity enhancement. We observed a remarkable improvement in electrical conductivity upon sulfur passivation and a significant contribution of electrons to thermal conductivity, which account for the enhanced thermal conductivity of the S-passivated InAs nanowires.